Level of information & communication technology (ICT) usage among ESL teachers in Malaysia - Hendehjan, Niyosha Morshedi; Noordin, Nooreen (Australian International Academic Centre, 2013)
The current study attempted to identify the level of (ICT) usage among ESL teachers, the difference between the level of ICT usage based on gender and age, the teachers’ perception towards ICT usage and the barriers faced by teachers. This study was a quantitative study using the descriptive survey approach. The total number of participants was 90 ESL student teachers. Data collection involved the use of a questionnaire and the results were analysed using descriptive and inferential statistics. Findings showed that the level of ICT among teachers was moderate to high. The findings also revealed that females used ICT more than males and younger teachers used ICT more than older teachers. In addition, the level of perceived ease of use and perceived usefulness was moderate to high and high respectively. The findings also indicated that the level of barrier among teachers was low.